Teacher Skills in Teaching Small Groups and Individually for Students at SDN 13 Palangki from Skinner's Behaviorist Theory Viewpoint - Rhahima Zakia; Maqomam Mahmud; Masril Masril (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
These basic teaching skills are important to develop in the present era, especially in today's primary school, because if a child aged 5 to 15 is more interested in gadgets than lessons, then the teacher has his own technique to make his pupils focus on the lesson, and thus the teaching skill action should be done by the teacher. The purpose of writing this article is to find out how the teacher's skills in teaching small groups and individuals at SDN 13 Palangki. Data collection methods used are observations and interviews. In qualitative research, data analysis is done cyclically, starting with data reduction and ending with data presentation and conclusion. The social behavioral paradigm focuses on the individual's relationship with its environment, which consists of a variety of social and non-social objects that produce consequences or changes in environmental factors that cause behavior changes. The results of this study show that teachers form small groups or individuals based on student differences, small groups, or individuals formed to improve the quality of interaction between students, small group and individuals can be used to make learning more effective, and teachers provide interesting material for students.